Nitrogen budgets and nitrogen use efficiency as agricultural performance indicators in Lake Victoria basin - Ntinyari, Winnie; Gweyi-Onyango, Joseph; Giweta, Mekonnen; Mutegi, James; Mochoge, Benson; Nziguheba, Generose; Masso, Cargele (Frontiers in Sustainable Food Systems, 2022)
Too little nitrogen (N) threatens sub-Saharan Africa's crop productivity and soil fertility (SSA). Nitrogen budgets (NB) and nitrogen use efficiency (NUE) are critical tools for assessing N dynamics in agriculture and have received little or no attention in the region. Data were collected from smallholder farmers clustered into two categories, farmers applying and farmers not applying N fertilizers. NB were calculated using the CHANS model approach for field and farm-level approaches. The results showed spatial variabilities in NB and NUE at the field level (maize and rice) all the catchments. At the field level, N balances were negative for the two crops in all the catchments. Similarly, at the farm gate, a deficit of -78.37 kg N ha -1 was observed, an indicator of soil N mining. NUE values at the field scale varied across the catchments for both crops, with values for maize grown without N ranging from 25.76% to 140.18%. Even with the application of mineral N at higher levels in rice fields compared to maize fields, NUE values ranged between 81.92% and 224.6%. Our study revealed that the Lake Victoria region suffers from inefficient N cycling due to depleted soil N pools and low synchrony between N input and N removal. Therefore, a challenge lies in exploiting more sustainable N sources for farmers in the region for sustainable cropping systems. The NB and NUE provide critical information to agriculture stakeholders to develop environmental, agronomic, and economically viable N management solutions